1981
DOI: 10.1530/acta.0.0970251
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay for 4-hydroxyoestrone in human urine

Abstract: Abstract. Under the protection of ascorbic acid a 4-hydroxyoestrone-bovine serum albumin conjugate was prepared containing intact 4-hydroxyoestrone as determined by gas chromatography-mass spectrometry. Using this antigen, antibodies with high affinity and specificity for 4-hydroxyoestrone were raised in rabbits. An assay procedure for the determination of 4-hydroxyoestrone in human urine and the assessment of its reliability are described. The following urinary excretion rates were found: male children 0.29 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…For the detection of estrogens and EMs in a culture cell, radio-or enzyme immunoassay is still the most popular technique [19][20][21][22]. However, the immunoassay is likely to suffer from poor specificity, accuracy, and reproducibility due to cross-reactivity and lot-to-lot variation of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…For the detection of estrogens and EMs in a culture cell, radio-or enzyme immunoassay is still the most popular technique [19][20][21][22]. However, the immunoassay is likely to suffer from poor specificity, accuracy, and reproducibility due to cross-reactivity and lot-to-lot variation of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Current methods for measuring endogenous estrogen metabolites have involved radioimmunoassay (RIA), enzyme immunoassay (EIA), , high-performance liquid chromatography (HPLC) with electrochemical detection, or stable isotope dilution combined with analysis using gas chromatography/mass spectrometry (GC/MS) . Although RIA and EIA can be sensitive, they often suffer from poor specificity, accuracy, and/or reproducibility due to the cross-reactivity and lot-to-lot variation of antibodies. Although HPLC with electrochemical detection has been used for estrogen metabolite analysis in hamsters treated with 17β-estradiol and in pregnant women whose estrogen levels are elevated at least 10-fold, it is relatively insensitive. Its specificity and accuracy for measuring endogenous level estrogen metabolites in human biological matrixes are questionable.…”
mentioning
confidence: 99%
“…It may be concluded that the 4-hydroxyoestrogens which have been shown to be potent hor¬ mones with regard to the induction of premature ovulation in PMSG treated immature rats (Ball et al 1979) and the induction of sexual behaviour in ovariectomized rats (Ball et al 1980) have a signifi¬ cant importance for uterine growth and vaginal opening but in this model no role in LH release.…”
Section: Discussionmentioning
confidence: 96%
“…Using the concentration of catechol¬ oestrogens given in the Method Section plasma levels of unconjugated 2-and 4-hydroxyoestrone as determined by radioimmunoassay Emons et al 1980) increase between 50 to 100 pg/ml thus leading to absolute levels of ap¬ proximately 300 pg/ml for 2-hydroxyoestrone and 80 pg/ml for 4-hydroxyoestrone. As checked by intense pre-testing of the pumps a fairly constant release rate which matches the fac¬ tory specifications within a range of 10% may be anticipated.…”
Section: Discussionmentioning
confidence: 99%